Positive psychology in L2 speaking: The predictive roles of foreign language speaking enjoyment, the ideal L2 speaking self, and L2 speaking grit - Fathi, Jalil; Behzadpoor, Seyyed-Foad (Studies in Second Language Learning and Teaching, 2025)
This study investigates the impact of positive psychology factors on English as a foreign language (EFL) learners’ second language (L2) speaking proficiency. Specifically, it examines the predictive roles of foreign language speaking enjoyment, the ideal L2 speaking self, and L2 speaking grit on L2 speaking proficiency. Data were collected from 271 EFL learners enrolled in IELTS speaking courses, utilizing validated scales and IELTS-based speaking tasks. Through structural equation modeling, relationships between psychological constructs and L2 speaking proficiency were analyzed. The results showed significant direct relationships between speaking enjoyment and L2 speaking proficiency, as well as between the ideal speaking self and proficiency. Crucially, L2 speaking grit was found to partially mediate the relationships between both enjoyment and L2 speaking proficiency, as well as the ideal self and L2 speaking proficiency. These findings underscore the importance of positive psychological factors in language learning, particularly highlighting the significant interplay of enjoyment, the ideal self, and grit in fostering L2 speaking development. The study provides insights for teachers, emphasizing the need to incorporate strategies that cultivate positive emotions, support the development of learners’ ideal L2 speaking self, and promote resilience in the face of challenges, ultimately leading to improved speaking skills.